The literal structure of sacred letters in contemporary Iraqi painting - Hayder Salih Abdullah; Ban Mohammad Ali (مجلة فنون البصرة, 2023)
This research is concerned with the study of (the lettering structure of the sacred letters in the contemporary Arabic formation), which worked on studying the structure of the Arabic letter within the limits of the sacred speech, and the great role that the speech played when it was embodied within the artistic works, whether it was drawing, sculpture or ceramics. The first is the preservation of Islamic heritage and arts, which were distinguished by the most important element in them, which is the Arabic letter and calligraphy, which gained their sanctity from the Noble Qur’an and the noble prophetic sayings. The researcher reached a number of results, including: 1- The contemporary literal structure of artistic discourses, with their different types and their preoccupations in Arabic formation, revealed divine connotations that are liberated from their rules. 2- Representing the literal structures in their abstract forms through dealing with the details, disposing of the mass, and manipulating the texture to broadcast a sacred discourse represented by simulating the essence, and by activating the technical feature within the formation of contemporary discourse and its data, which is a procedure to introduce sacred connotations to convey the meaning and undermine the similarity and simplify it with plastic and semantic dimensions.